Effects of Semaglutide on Stroke Subtypes in Type 2 Diabetes: Post Hoc Analysis of the Randomized SUSTAIN 6 and PIONEER 6 - Strain, W. David; Frenkel, Ofir; James, Martin A.; Leiter, Lawrence A.; Rasmussen, Søren; Rothwell, Peter M.; Sejersten Ripa, Maria; Truelsen, Thomas C.; Husain, Mansoor (Stroke (1970), 2022)
GLP-1 RA (glucagon-like peptide-1 receptor agonists), including semaglutide, may reduce stroke risk in people with type 2 diabetes. This post hoc analysis examined the subcutaneous and oral semaglutide effects, versus placebo, on stroke and its subtypes in people with type 2 diabetes at high cardiovascular risk. SUSTAIN 6 (Trial to Evaluate Cardiovascular and Other Long-Term Outcomes With Semaglutide in Subjects With Type 2 Diabetes) and PIONEER 6 (Peptide Innovation for Early Diabetes Treatment) were randomized cardiovascular outcome trials of subcutaneous and oral semaglutide in people with type 2 diabetes at high cardiovascular risk, respectively. Time to first stroke and stroke subtypes were analyzed using a Cox proportional hazards model stratified by trial with pooled treatment as a factor. The impact of prior stroke, prior myocardial infarction or stroke, age, sex, systolic blood pressure, estimated glomerular filtration rate, and prior atrial fibrillation on treatment effects was assessed using interaction values. Risk of major adverse cardiovascular event was analyzed according to prior stroke. A total of 106/6480 participants had a stroke (1.0 event/100 patient-years of observation [PYO]). Semaglutide reduced incidence of any stroke versus placebo (0.8 versus 1.1 events/100 PYO; hazard ratio, 0.68 [95% CI, 0.46-1.00]; =0.048), driven by significant reductions in risk of small-vessel occlusion (0.3 versus 0.7 events/100 PYO; hazard ratio, 0.51 [95% CI, 0.29-0.89]; =0.017). Hazard ratios for risk of any stroke with semaglutide versus placebo were 0.60 (95% CI, 0.37-0.99; 0.5 versus 0.9 events/100 PYO) and 0.89 (95% CI, 0.47-1.69; 2.7 versus 3.0 events/100 PYO) in those without and with prior stroke, respectively. Except for prior atrial fibrillation ( =0.025), no significant interactions were observed between treatment effects on risk of any stroke and subgroups investigated, or between treatment effects on risk of major adverse cardiovascular event and prior stroke ( >0.05 for all). Semaglutide reduced incidence of any first stroke during the trials versus placebo in people with type 2 diabetes at high cardiovascular risk, primarily driven by small-vessel occlusion prevention. Semaglutide treatment, versus placebo, lowered the risk of stroke irrespective of prior stroke at baseline. URL: https://www. gov; Unique identifier: NCT01720446 and NCT02692716.